2015
DOI: 10.1093/pcp/pcv102
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Gene Expression/Deletion Systems forMarchantia polymorphaUsing its Own Heat-Shock Promoter and Cre/loxP-Mediated Site-Specific Recombination

Abstract: The liverwort Marchantia polymorpha is an emerging model plant suitable for addressing, using genetic approaches, various evolutionary questions in the land plant lineage. Haploid dominancy in its life cycle facilitates genetic analyses, but conversely limits the ability to isolate mutants of essential genes. To overcome this issue and to be employed in cell lineage, mosaic and cell autonomy analyses, we developed a system that allows conditional gene expression and deletion using a promoter of a heat-shock pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…We therefore generated Cre/ lox P-mediated conditional knock-out sectors (Mp arf2-1 cko and Mp arf2-2 cko ; Ref. 22,23) through heat-shock and DEX-inducible deletion of a CRISPR-resistant Mp ARF2 gene in a background with a CRISPR/Cas9-induced mutation in the endogenous Mp ARF2 gene ( Fig. S8a,b ).…”
Section: Figmentioning
confidence: 99%
“…We therefore generated Cre/ lox P-mediated conditional knock-out sectors (Mp arf2-1 cko and Mp arf2-2 cko ; Ref. 22,23) through heat-shock and DEX-inducible deletion of a CRISPR-resistant Mp ARF2 gene in a background with a CRISPR/Cas9-induced mutation in the endogenous Mp ARF2 gene ( Fig. S8a,b ).…”
Section: Figmentioning
confidence: 99%
“…The liverwort Marchantia polymorpha is an emerging model plant among the basal land plants, owing to several advantages for genetic studies: a low-genetic redundancy, a haploid-dominant life cycle, and tractable genetic tools, such as high-efficiency transformation methods and genetic technologies (Ishizaki et al, , 2016Kubota et al, 2013;Sugano et al, 2014;Eklund et al, 2015;Kato et al, 2015;Flores-Sandoval et al, 2016;Nishihama et al, 2016). Since liverworts represent an early divergent lineage of extant land plants (Qiu et al, 2006), investigations using liverworts are of particular interest in terms of land plant evolution.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, transgenic PMpHSP17.8 lines of M. polymorpha were generated, which expressed mVenus yellow fluorescent protein (YFP) 40 under control the endogenous heat-responsive MpHSP17.8 promoter. It was previously shown that incubation of transgenic M. polymorpha at 37°C for 1 h induced a P MpHSP17.8 -controlled targeted gene by approximately 700-fold 42 .…”
Section: Resultsmentioning
confidence: 97%